The clinical and laboratory characteristics of infectious mononucleosis caused by the Epstein-Barr virus type 1 in hospitalized children - M. I. Popkova; O. V. Utkin; E. A. Soboleva; E. N. Filatova; D. A. Bryzgalova; N. A. Sakharnov (Журнал инфектологии)
Aim. The aim of the study was to provide clinical and laboratory characteristics of infectious mononucleosis caused by Epstein-Barr virus (EBV) genotype 1 in hospitalized children.  Materials and methods. The material of the study was blood leukocytes and saliva of children aged 1-17 years, hospitalized with a diagnosis of infectious mononucleosis caused by EBV (n=67). For differential detection of EBV-1/ EBV-2, we used an optimized one-round PCR variant with electrophoretic detection of amplification products in agarose gel. Clinical symptoms and laboratory data of patients were analyzed separately and combined into groups of signs. Statistical data processing was carried out using the R programming language and the RStudio environment.  Results. In all children, only one type of virus (EBV-1) was detected in blood leukocytes and saliva. The first data on clinical and laboratory signs of EBV-1 infectious mononucleosis, characterized by a typical symptom complex, have been obtained. The age criterion for dividing patients into groups of younger (1–5 years) and older (6–17 years) age, which were characterized by the most pronounced differences in the manifestations of overt EBV-1 infection, was determined. In young children, the leading was the syndrome of intoxication, in older children, signs of cytolytic syndrome were more pronounced. According to laboratory data, in the age group of 1–5 years, monocytopenia and a decrease in hemoglobin were more often observed, and in children of 6–17 years, lymphocytosis, monocytosis, elevated levels of hepatic transaminases and hemoglobin.  Conclusion. For the first time, EBV typing was performed in children with infectious mononucleosis. The dominant genotype of the virus in infectious mononucleosis in children living in the territory of a large city in the European part of Russia is EBV-1. For the first time, the characteristics of EBV-1 infection are given. The data obtained on the different severity of clinical and laboratory signs of the disease are prerequisites for continuing research aimed at finding the relationship between the characteristics of the clinical course of the infection and the genetic heterogeneity of the EBV population.